A Rare Cause of Reversible Renal Hemosiderosis - Rima Abou Arkoub; Don Wang; Deborah Zimmerman (Case Reports in Nephrology)
Kidney failure secondary to renal hemosiderosis has been reported in diseases with intravascular hemolysis, like paroxysmal nocturnal hemoglobinuria, and valvular heart diseases. We present here a case of hemosiderin induced acute tubular necrosis secondary to intravascular hemolysis from Clostridium difficile infection with possible role of supratherapeutic INR. We discuss the pathophysiology, causes, and prognosis of acute tubular injury from hemosiderosis.